Evaluation of Mean Platelet Volume in Children with Hypertension - Ismail Yildiz; Ozgur Kizilca (International Journal of Hypertension)
Background. Childhood hypertension, a disease with increasing prevalence, can lead to severe health problems. With the increased pressure on the vascular endothelium in hypertension, lesions in the endothelium result in endothelial activation and a process of inflammation, which causes platelet activation and in the bone marrow the release of platelet precursor cells into the peripheral blood stream. During inflammation, changes in the number and size of platelets are observed. With the release of platelet precursors into the peripheral blood stream due to platelet activation, an increase in mean platelet volume (MPV) is also seen. Aim. Our aim in this study is the evaluation of MPV changes in the hemogram of children suffering from hypertension, a condition causing severe cardiovascular problems. Material and Methods. This research is a descriptive retrospective cross-sectional study. It consists of a patient group diagnosed with hypertension and a control group of children presenting for routine check-ups with no diagnosed hypertension. Demographic characteristics, arterial pressure values, and hemogram parameters have been evaluated. Results. A total of 90 cases were enrolled in the study, including a patient group of 45 cases with hypertension (19 females, 26 males) and a control group of 45 cases (27 females, 18 males). The median age was 15 years in the hypertension group and 13 years in the control group. In the hypertension cases, the thickness of the carotis intima media was statistically significantly greater than in the control group (p < 0.001). Echocardiographic findings (IVSd, LVDd, LVPWd, IVSs, LVDs, LVPWs, and LV mass) were significantly higher in the hypertension group compared to the control group (p < 0.001). A statistically significant difference in platelet count and MPV values between the groups was not found (p = 0.151, p = 0.405, respectively). Conclusion. While MPV is hypothesized to be higher in hypertensive individuals, there was no statistically significant difference between the hypertensive and non-hypertensive groups in this study.